2018
DOI: 10.1136/thoraxjnl-2018-212104
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for situs defects and congenital heart disease in primary ciliary dyskinesia

Abstract: Primary ciliary dyskinesia (PCD) is associated with abnormal organ positioning (situs) and congenital heart disease (CHD). This study investigated genotype-phenotype associations in PCD to facilitate risk predictions for cardiac and laterality defects. This retrospective cohort study of 389 UK patients with PCD found 51% had abnormal situs and 25% had CHD and/or laterality defects other than situs inversus totalis. Patients with biallelic mutations in a subset of nine PCD genes had normal situs. Patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 10 publications
6
62
1
Order By: Relevance
“…The distribution of cardiac situs according to the mutated PCD genes showed that patients with mutations in PCD genes can have either normal or abnormal cardiac situs. As expected, only normal cardiac situs (levocardia) was reported in patients with mutations in a specific subset of PCD genes including genes encoding central complex components ( HYDIN ), radial spokes components ( RSPH9 , RSPH4A , DNAJB13 ) and genes essential for multiciliogenesis ( CCNO ) (Figure A,B).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The distribution of cardiac situs according to the mutated PCD genes showed that patients with mutations in PCD genes can have either normal or abnormal cardiac situs. As expected, only normal cardiac situs (levocardia) was reported in patients with mutations in a specific subset of PCD genes including genes encoding central complex components ( HYDIN ), radial spokes components ( RSPH9 , RSPH4A , DNAJB13 ) and genes essential for multiciliogenesis ( CCNO ) (Figure A,B).…”
Section: Resultssupporting
confidence: 85%
“…Affected individuals present with a range of nonspecific manifestations including chronic wet cough, rhinosinusitis, otitis media and hearing impairment. About 50% of patients have laterality problems . Infertility is frequently present in affected adult males …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first link between cilia and LR asymmetry was inspired by the observation that patients with PCD often have SIT (Sutherland & Ware, 2009). Three past studies investigated the accurate rates of laterality defects in PCD, with combined results showing 41.0%-47.7% of patients with PCD had SIT (Best et al, 2019;Shapiro, Davis, & Ferkol, 2014;Shapiro et al, 2007). On the other hand, careful screening for PCD in SIT cases is still necessary.…”
Section: Discussionmentioning
confidence: 99%
“…We classified cases as situs ambiguous if any of the abnormalities was detected, such as mesocardia or isolated dextrocardia, absent/interrupted inferior vena cava, atrial isomerism or atrial situs ambiguous, bronchial isomerism or pulmonary isomerism, thoracic SI, polysplenia or asplenia, midline liver, abdominal SI and (2) SIT, defined as complete mirror‐imaged arrangement of thoracic and abdominal organs. The diagnosis of SIT refered to the study by Best et al () and Kennedy et al (). If the stomach and heart were on the right, liver on the left, the patients were assumed to have SIT, unless detailed imaging reports to suggest situs ambiguous.…”
Section: Methodsmentioning
confidence: 99%